Changing attitude into behavior: How to reduce carbon dioxide emissions. (31st March 2021) - Sumrall, William J.; Sumrall, Kristen M.
Abstract: This article's focus was on transitioning middle grade students from the position of having a positive environmental attitude toward their exhibiting actual behaviors that address climate change. Using research by Newhouse's criteria of changing attitude into behavior, specific activities were developed and tested in a eighth grade classroom. The 5E model of instruction was the strategy used to build the series of activities. Thus, we began the class with a series of engaging questions for discussion to differentiate between attitudes and behaviors. Building a knowledge base about the negative outcomes of climate change as well as new technologies that exist to reduce carbon dioxide emissions were the initial explorations and strategies used to move students from attitude to behavior. The groups' development and implementation of classroom presentations where they learn about negative climate change outcomes and the technologies available to address these outcomes were described. Discerning what was accurate Internet information and post presentation discussions were some of the review strategies used for explanation to occur. The two foundation building presentation activities were followed by two behavior-based activities (i.e., extension/elaboration ) for the purpose of moving students from positive attitudes to positive behaviors with regard to addressing climate change.